First Global Survey of Evidences the Ichnogenus Osedacoides and it Relates to the Rezent Zombie-Worms Osedax (Global Journal of Science Frontier Research, 2016)
Abstract not found
Keywords: ichnofossils; cladistic analysis; osedax like worms; osedacoides; overview